IMPLEMENTASI SISTEM PENJAMINAN MUTU INTERNAL (SPMI) DI SD YPPK GEMBALA BAIK KOTA JAYAPURA PROVINSI PAPUA - Kuswanto, Kuswanto; Mataputun, Yulius; Bharanti, Elita (NOKEN : Jurnal Pengelolaan Pendidikan, 2021)
This study aims to analyze the implementation of the steps of the Internal Quality Assurance System (quality mapping, preparation of quality compliance plans, implementation of quality compliance, evaluation of quality audits and preparation of standards on National Standard in Education) at SD YPPK Gembala Baik, Jayapura City, Papua Province. This study used a qualitative descriptive approach to a case study design. The object of research is the principal, the head of school quality assurance, the quality coordinators and the head of the school committee. The data collection techniques used participatory observation, in-depth interviews, and checking documentation. The validity test of the data used data credibility techniques, namely triangulation, observation persistence, and peer discussion. Data analysis: data reduction, data display, and conclusion / verification. The results of this study indicate that in general, SD YPPK Gembala Baik, Jayapura City, Papua Province has implemented the SPMI steps properly according to the SPMI-Dikdasmen implementation guidelines in the following forms of activities. (1) lead the quality mapping process, ensure that the responsibility for quality mapping is shared and become part of school management, directs all school members to work together, focuses on evaluating and improving school quality; (2) planning for quality compliance through compiling RKS / RKAS documents; (3) carry out the fulfillment of quality by determining the person in charge and schedule, allocation of funding, according to conditions, and reporting of programs / activities; (4) carry out evaluation / internal audit by establishing evaluation indicators, compiling instruments, collecting data, analyzing and preparing recommendations; and (5) formulating new quality standards by implementing benchmarking, accessing rules related to SNP, studying and formulating quality indicators and their criteria in accordance with SNPs, socializing regulations, formulating indicators and establishing them with stakeholders as a reference for the initial quality of education.Keywords: internal; quality assurance systemÂ